Assessing suffering in experimental pain models: psychological and psychophysiological correlates - Brunner, Michael; Flor, Herta (Zeitschrift für Psychologie, 2017)
Although suffering is a central issue in pain, there is only little research on this topic. The aim of this study was to assess suffering in an experimental context using various stimulation methods and durations, and to examine which psychological or psychophysiological measures covary with pain-related suffering. Twenty-one healthy volunteers participated in two experiments in which we used tonic thermal and phasic electric stimuli with short and long stimulus durations. The participants rated pain intensity, unpleasantness, and pain-related suffering on separate visual analog scales (VAS) and completed the Pictorial Representation of Illness and Self Measure (PRISM), originally developed to assess suffering in chronic illness. We measured heart rate, skin conductance responses (SCRs), and the electromyogram (EMG) of the musculus corrugator supercilii. For both heat and electric pain, we obtained high ratings on the suffering scale confirming that suffering can be evoked in experimental pain conditions. Whereas pain intensity and unpleasantness were highly correlated, both scales were less highly related to suffering, indicating that suffering is distinct from pain intensity and unpleasantness. Higher suffering ratings were associated with more pronounced fear of pain and increased private self-consciousness. Pain-related suffering was also related to high resting heart rate, increased SCR, and decreased EMG during painful stimulation. These results offer an approach to the assessment of suffering in an experimental setting using thermal and electric pain stimulation and shed light on its psychological and psychophysiological correlates.
Gesehen am 22.05.2018